2008
DOI: 10.1007/s11999-008-0486-y
|View full text |Cite
|
Sign up to set email alerts
|

A New Digital Preoperative Planning Method for Total Hip Arthroplasties

Abstract: Preoperative templating is an important part of a THA. The ability to accurately determine magnification of the hip on the radiograph and apply identical magnification to the radiograph and template will improve accuracy of preoperative templating of THA. We designed a templating method using a new way of determining the hip magnification with a linear relationship between magnification of the hip and the reference object on top of the pubis symphysis; the relationship was determined on 50 radiographs. We then… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
39
0
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 25 publications
(46 reference statements)
8
39
0
4
Order By: Relevance
“…Intraobserver ICC values showed almost perfect agreement (ICC [ 0.8) for both acetabular and femoral components when using both templating methods, suggesting both methods are highly reproducible. Our ICC values correspond well to previous studies, which found ICC values ranging from 0.7 to 0.97 [6,10,15,21]. Our study showed that experience level did not have an effect on accuracy nor intraobserver variability.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Intraobserver ICC values showed almost perfect agreement (ICC [ 0.8) for both acetabular and femoral components when using both templating methods, suggesting both methods are highly reproducible. Our ICC values correspond well to previous studies, which found ICC values ranging from 0.7 to 0.97 [6,10,15,21]. Our study showed that experience level did not have an effect on accuracy nor intraobserver variability.…”
Section: Discussionsupporting
confidence: 92%
“…However, to the best of our knowledge, no study has shown that errors in templating at the time of surgery directly leads to inferior clinical outcomes. Our study found substantial interobserver ICC value agreement for acetate templating for the femoral component and digital templating for the acetabular and femoral components, which is similar to several studies using the analog or digital templating methods [6,15]. However, values were lower than that quoted by Gamble et al [10], which found ICC values ranging from 0.8 to 0.94.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…With the development of digital images, this conventional technique is gradually becoming impractical because film-based radiographs may no longer exist. Some studies have reviewed the utility of a digital templating technique [3,5,9,10,12,14,19], but most of them focussed on comparison of the accuracy between acetate templating and digital templating [3,9,10,12,14,19]. In most of these studies, the primary diagnosis of THA was osteoarthritis or was not specified (Table 1).…”
Section: Introductionmentioning
confidence: 99%